Perkembangan Institusi Islam di Sarawak Sebelum Pembentukan Malaysia: Progression of Islamic institution in Sarawak before the formation of Malaysia - Abdul Kadir, Abdul Razak; Bujang, Saimi; Awang Ahmad, Awang Nib Zuhairi; Towpek, Hadenan (Journal of Al-Tamaddun, 2023)
From the rule of the Sultanate of Brunei to the colonialism of James Brooke in Sarawak shown the political and geographical landscape completely change. Historically James Brooke starts to intervene in Sarawak affairs. He starts conquered from Tanjung Datu to Batang Samarahan turned into a huge territory due to the requisition of James Brooke to hand over some areas under Brunei from Simanggang to the border region of Brunei. Brooke’s positioning until the Second World War caused the entire administration invaded by western colonialism in Sarawak. Based on original agreement between Brunei and Brooke Families, the later was to control the administration and economic development and must not interfere with the customs of the Malays and Islam, but in the end, colonialism is almost absolute. This includes Islamic law in the era of James Brooke which introduced Native Mohammedan Probate and Divorce Court. Thus, this article objectives to describe the development from the aspect of Islamic institutions and the sociology of the Islamic community in Sarawak. This article applies the historical method of Kuntowijoyo namely heuristics (collection of historical material), internal and external criticism, historical interpretation, and historiography. This article shows that the pressure of the British government after Sarawak was handed over by Vyner Brooke to the British did not tarnish the Islamic institutions that were established in Brooke’s time and after. However, the socio-Islamic society is influenced by western culture.